Poverty Reduction Policy of Small Farmers and Culturers Towards Explpoitative Middlery Intermediation - Bambang Arwanto (Eduvest - Journal of Universal Studies, 2022)
The poverty process creates specific rural poverty groups in a complex and multidimensional phenomenon, so that no valid anti-poverty program can apply equally to every time and every region, one of the specific rural poverty community groups created by the poverty process is Small Farmers and Cultivators, the source of their poverty is due to low access to land and capital, the alternatives available to them in the labor market are very small with low wages, precarious work, high unemployment rates, and limited land, so they experience exploitation by middlemen. intensive. The type of research used is descriptive research, the approach used is a case study using the PRA (Participatory Rural Appraisal) method. In this case, the case study is the search for problems (problem structuring) of the sources and processes behind the poverty of the farming community in Jonggon Kampung Village and the policies that need to be implemented in response to these problems. The research location was conducted in Kutai Kertanegara Regency, East Kalimantan Province, the unit of analysis of this study was at the village level, the determination of the unit of analysis was carried out intentionally according to the research objectives (purposive), namely villages according to the classification of poor villages with a functional group approach of people who are vulnerable to the poverty process. rural areas, namely groups of small farmers and sharecroppers. The results of the study confirm the policies that need to be implemented in an effort to increase the productivity of poor farmers in Jonggon Kampung Village, namely; controlling the shrinkage of functional land, increasing the application of appropriate technology, capital assistance and increasing access to marketing as alternative selected policies to be recommended.